Interdisciplinary Collaboration between Natural and Social Sciences – Status and Trends Exemplified in Groundwater Research - Barthel, Roland; Seidl, Roman (PloS one, 2017)
Interdisciplinary collaboration, particularly between natural and social sciences, is perceived as crucial to solving the significant challenges facing humanity. However, despite the need for such collaboration being expressed more frequently and intensely, it remains unclear to what degree such collaboration actually takes place, what trends and developments there are and which actors are involved. Previous studies, often based on bibliometric analysis of large bodies of literature, partly observed an increase in interdisciplinary collaboration in general, but in particular, the collaboration among distant fields was less explored. Other more qualitative studies found that interdisciplinary collaboration, particularly between natural and social scientists was not well developed, and obstacles abounded. To shed some light on the actual status and developments of this collaboration, we performed an analysis based on a sample of articles on groundwater research. We first identified journals and articles therein that potentially combined natural and social science aspects of groundwater research. Next, we analysed the disciplinary composition of their authors' teams, cited references, titles and keywords, making use of our detailed personal expertise in groundwater research and its interdisciplinary aspects. We combined several indicators developed from this analysis into a final classification of the degree of multidisciplinarity of each article. Covering the period between 1990 and 2014, we found that the overall percentage of multidisciplinary articles was in the low single-digit range, with only slight increases over the past decades. The interdisciplinarity of individuals plays a major role compared to interdisciplinarity involving two or more researchers. If collaboration with natural sciences takes place, social science is represented most often by economists. As a side result, we found that journals publishing multidisciplinary research had lower impact factors on average, and multidisciplinary papers were cited much less than mono-disciplinary ones.